2015
DOI: 10.1590/1983-40632015v4537332
|View full text |Cite
|
Sign up to set email alerts
|

Métodos para superação de dormência em sementes de tomateiro arbóreo (Solanum betaceum)

Abstract: RESUMO O tomateiro arbóreo (Solanum betaceum) é espécie pouco conhecida, porém, apresenta frutos com enorme potencialidade de mercado, uma vez que podem ser consumidos tanto in natura como na forma industrializada. Contudo, um dos entraves para essa potencialidade se tornar realidade é a produção de mudas. A propagação dessa espécie ocorre por meio de sementes, mas, normalmente, a germinação requer tempo, principalmente sob condições de estresse. Objetivou-se verificar se existe dormência em sementes de tomate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(10 reference statements)
0
5
0
1
Order By: Relevance
“…Typically, tree tomato is propagated by seeds that have uneven germination, which may be related to dormancy (Neto et al, 2015). This characteristic is common in seeds of other Solanaceae species, such as Solanum chenopodioides (Cabrera et al, 2010), which have slow and irregular germination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, tree tomato is propagated by seeds that have uneven germination, which may be related to dormancy (Neto et al, 2015). This characteristic is common in seeds of other Solanaceae species, such as Solanum chenopodioides (Cabrera et al, 2010), which have slow and irregular germination.…”
Section: Resultsmentioning
confidence: 99%
“…Dormancy in freshly extracted seeds is thought to reduce the germination of tree tomato seeds. Tree tomato propagation is mainly by seed (Neto et al, 2015), and seedling emergence of tree tomato seeds is low and uneven, deterring the formation of quality seedlings. Dormancy is also a problem directly related to germination and storage of tree tomato seeds (Neto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the physical and chemical characteristics of tamarillo fruits (Table 4) positive photoblastic and present latency of photo [26].…”
Section: Resultsmentioning
confidence: 99%
“…This behavior was also evidenced in Solanum aethiopicum by Jorge et al (2019), who observed that the application of GA 3 increased seed germination on the 6 th (50%) and 14 th days (77%), respectively at doses of 247 and 218 mg.L -1 . Kosera Neto et al (2015), by evaluating different methods to improve seed germination rate in Solanum betaceum, demonstrated that GA 3 application leads to increases of 90% in this variable.…”
Section: Resultsmentioning
confidence: 99%